Численное моделирование течений вязкой несжимаемой жидкости с использованием неявной квазимонотонной схемы годунова повышенной точности - Русанов, Андрей Викторович; Косьянов, Дмитрий Юрьевич (Eastern-European Journal of Enterprise Technologies, 2014)
The application of an implicit quasi-monotone high accuracy Godunov type scheme to the numerical simulation of the viscous incompressible flow is viewed. The divergent and undivergent forms of the Euler and Navier-Stokes equations with pseudo-compressible term are presented. The appropriate boundary conditions and complementary relations are given. Several representative problems have been solved and comparison with the theoretical data and the experimental data and other numerical solutions showed good agreements.